Membangun Konsep Organisasi Autentik. Kajian Metaetnografi - Sus Budiharto; Fathul Himam; Bagus Riyono; Arief Fahmi (Faculty of Psychology Universitas Gadjah Mada, 2019)
Facing the “VUCA world” (Volatility, Uncertainty, Complexity, Ambiguity), organizations need strategies to sustain and keep growing. The aim of this research is constructing authentic organization as alternative concept for organizations in coping with those rapid changes. However, the concept of authentic organization is not solid yet. This research explores and builds the concept of authentic organization. Using seven steps of meta-ethnography approach for 33 relevant articles, this study offers two main findings: The first is the definition of authentic organization and the second is Truthfulness, Resilience, Uncertainty friendly, and Eminence (“TRUE”) as the factors of authentic organization.